Genetic and environmental effects on parturition and lactation intervals in water buffaloes from Brazil - Souza Carneiro, P. L.; Mendes Malhado, C. H.; Antunes de Mello Affonso, P. R.; Ramos, A. de Amorim [UNESP] (Pagepress Publ, 2007)
Genetic and environmental effects on parturition interval (PI) and duration of lactation (DL) were evaluated in 107 Jafarabadi, 98 Mediterranean, 1027 Murrah and 624 crossbred buffalo females (n=1856), based on data from the Buffalo Genetic Improvement Program-PROMEBUL from 1980 to 2003. The statistical model included effects of herd, parturition year and month, calf's sex, parturition order and genetic group, composing 11, 34, 12, 2, 12 and 4 classes, respectively. A significant effect over PI was observed (P<0.01) in all classes, excepting sex. Mean parturition intervals per genetic group presented significant differences through SNK test (P<0.05), with mean values of 451.29; 429.47; 406.97 and 389.78 days in Mediterranean, crossbred, Murrah and Jafarabadi, respectively. Mean DL values were 276.68; 270.33; 258.03 and 235.59 days for Mediterranean, Murrah, crossbred and Jafarabadi groups, respectively. No significant differences in DL were observed in relation to genetic groups. However, herd and parturition order, year and month significantly influenced DL (P<0.01). The herd was the main source of variation over DL, followed by parturition year and month. A regression based on parturition month in relation to PI and DL showed that females giving birth in the last months of the year presented higher PI and DL.
Keywords: Mediterranean; Murrah; Jafarabadi